Multiple cerebral gliomas in multiple sclerosis - Reagan, T. J. (1973)
A patient with multiple sclerosis and a multicentric anaplastic astrocytoma is described. The evidence suggests that the relationship is not coincidental and that the astrocytomas originate in multiple sclerosis plaques.